STRUCTURE OF PROFESSIONAL-PRACTICAL COMPETENCE OF STUDENTS IN THE DESIGN (COSTUME) EDUCATIONAL PROGRAM (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This thesis examines the structure and essence of professional-practical competence among students enrolled in design education programs, specifically within the field of costume design. The study analyzes the integration of artistic, technological, communicative, and reflective components that shape the holistic professional competence of future costume designers. It highlights how creative thinking, technical mastery, and socio-cultural awareness interact in the learning process to form a competent, innovative specialist capable of translating artistic concepts into practical fashion solutions.